Management of paediatric laryngotracheal trauma. Issue 11 (5th November 2022) - Li, H; Li, Z; Zhao, J; Wang, G; Wang, H; Zhang, F; Sun, N; Han, Y; Zhang, J; Ni, X
Abstract: Objective: To summarise and describe the clinical presentations, diagnostic approaches and airway management techniques in children with laryngotracheal trauma. Methods: The clinical data related to laryngotracheal trauma diagnosed and treated at the Beijing Children's Hospital, between January 2013 and July 2018, were retrospectively reviewed. Disease diagnosis, treatment, management and outcomes were analysed. Results: A total of 13 cases were enrolled, including 7 cases of penetrating laryngotracheal trauma. The six cases of blunt laryngotracheal trauma were caused by collisions with hard objects. In all cases, voice, airway and swallowing outcomes were graded as 'good', except for one patient who had residual paralysis of the vocal folds. Conclusion: Flexible fibre-optic laryngoscopy and computed tomography can play an important role in diagnosing laryngotracheal trauma. The airway should be secured and, if necessary, opened by tracheal intubation or tracheostomy.